Duck! Rabbit! - Rosenthal, Amy Krouse; Lichtenheld, Tom (San Francisco, Calif. : Chronicle Books, 2009)
Two unseen characters argue about whether the creature they are looking at is a rabbit or a duck.
Parents' Choice, January 2009.
Wilson's Children, October 2010.
Notable/Best Books (A.L.A.), January 2010.
School Library Journal, May 2009.
Booklist starred, April 2009.
Pub Weekly, March 2009.
Keywords: Animals -- Identification -- Juvenile fiction; Animals -- Identification -- Fiction; Animals -- Fiction